PRO DAN KONTRA UNDANG-UNDANG NOMOR 8 TAHUN 2016 TENTANG PENYANDANG DISABILITAS - Denda Devi Sarah (Universitas Jenderal Ahmad Yani, 2020)
In this paper the author will discuss the pros and cons of the deliberation process of Law no. 8 of 2016 the hospitality of the nation that caters to people with disabilities, whether it is difficult access to public facilities, being excluded, etc. So that in this paper the author will look at whether the new law rules suit the needs of persons with disabilities, and when this rule is made, whether legislators are involved with people with disabilities in the law-making process, and what are the reasons the legislators change this regulation. . The method used in this paper uses normative law, the data used comes from the results of previous research, news or newspapers, laws. The results of this paper indicate that the making of laws is based on the needs of persons with disabilities. In addition, in the process, many actors, NGOs are involved to see the needs of persons with disabilities.